Theoretical studies of increasing the efficiency of mass transfer of magnetite suspension based on changes in the hydrodynamic parameters of the decontamination process - A.Y. Kryvenko; O.V. Bulakh; T.A. Oliinyk; S.A. Ruban (Технічна інженерія, 2025)
The article presents an improvement in the technology of iron ore enrichment by increasing the efficiency of gravity-hydraulic enrichment in radial thickeners of the MD9 type, which consists in the development of a new method for forming the output power of the device. Studies of the flow of magnetite suspension from the feeding device of a magnetic deslimer are presented, which allow us to obtain the dependences of the speed of movement of the feed flow of pulp and the content of solid on the parameters of the feed device of the initial suspension. The obtained dependences make it possible to reduce the negative impact of a flooded jet on the hydraulic enrichment of iron ore raw materials. Applying the well-known laws of hydrodynamics and hydraulics, a mathematical model of the separation of iron ore raw materials at the output of the power supply device of the magnetic deslimer device was constructed, according to which theoretical prerequisites are used when choosing the model structure. Calculations have obtained the dependence of the velocity of movement of solid phase particles of the pulp on the design features of the magnetic deslimer. Mathematical modeling is performed by applying a theoretical model of gravitational-hydraulic separation of iron ore raw materials in a magnetic deslimers. Equations were obtained that made it possible to significantly reduce the number of parameters that affect the course of the magnetic desolation process. A computational experiment based on the results of modeling the process of hydraulic-gravitational separation of suspensions in a magnetic desiccant made it possible to study the change in the corresponding parameters and their effect on the desiccation process. In turn, in practice, questions arise about finding quantitative relations. Therefore, it is necessary to conduct experimental studies on real magnetic deslimers in order to collect material for evaluating the parameters that are included in mathematical models. The presented mathematical models can vary the necessary parameters of the magnetic desolation process, taking into account the design features of the device itself and the power supply device, in order to obtain the final product of a given quality.